High-precision floating-point arithmetic in scientific computation - Bailey, D.H. (Computing in science & engineering, 2005)
IEEE 64-bit floating-point arithmetic is sufficient for most scientific applications, but a rapidly growing body of scientific computing applications requires a higher level of numeric precision. Software packages have yielded interesting scientific results that suggest numeric precision in scientific computations could be as important to program design as algorithms and data structures.